Upaya Meningkatkan Kompetensi Guru Menggunakan Media Pembelajaran ICT melalui Supervisi dengan Teknik Individual di Sekolah Dasar - Rusmiyati, S (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2018)
Abstract. The  of this study was to improve teacher competence in SD Negeri Kalinanas in using ICT learning media. The study was conducted in SD Negeri 1Kalinanas for ± 5 months starting Friday, July 22, 2016 until Saturday, November 19,2016. The subjects of this study were 9 teachers. Data collection is done throughinterviews, observation and documentation. From the interviews, the results show that it is important to use ICT learning media very well. The study was conducted in 2 cycles. In the pre cycle, the average score was 78 with a percentage of 53% achievement of all teachers in the research indicators for the use of ICT learning media, in the first cycle 88 average values were obtained with 69% achievement of all teachers in the research indicators of ICT learning media use, and in cycle II obtained an average value of 97 with a percentage of 88% achievement of all teachers in the research indicators of the use of ICT learning media. There has been an increase in teacher competency in the use of ICT learning media after being supervised with individual techniques by the principal of SD Negeri 1 Kalinanas.